Confirmatory factor analysis - Harrington, Donna (Oxford : Oxford University Press, 2009)
The author provides social work researchers with an essential roadmap to the highlights of confirmatory factory analysis (CFA)'s powers & how to harness them. The text includes an easy-to-follow overview of the method, step-by-step guides to creating a CFA model & assessing its fit, & explanations of the requirements for using CFA.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social service -- Research; Evaluation research (Social action programs); Evidence-based social work